Causativity in zero and overt nominalizations: An experimental study - Gianina Iordăchioaia; Jeannique Darby (Linguistica Pragensia)
We experimentally evaluate three patterns of deverbal nominalizations derived by means of zero, -ing and Romance suffixes (i.e., -(at)ion, -ment, and -ance) in English as to whether they can express causativity and anticausativity like their base verbs. We report the results of a first study which uses native speaker judgments to test the acceptability of these competing nominalizing suffixes (-ing vs. zero and -ing vs. Romance suffixes) in realizing event readings with argument structure inherited from their causative, and respectively, anticausative base verbs. While previous literature claims that zero cannot realize the structurally more complex causative readings, and -ing cannot realize anticausative readings, our current results indicate that all three suffixes may realize both types of readings. This is in line with data attested in natural text corpora and suggests that zero suffixes are not necessarily structurally simpler than overt suffixes as often claimed in previous literature.